USING GOOGLE JAMBOARD TO TEACH WRITING SKILL - MARWAH, M.Pd MARWAH (Journal of English Education and Linguistics, 2022)
This paper explains about how to use Google Jamboard as a digital media to teach English language with the subject of writing skill. This paper does not use a research methodology because the content of this paper is an explanation of the Google Jamboard, identification of the tools and their use in the Jamboard, and also strategies for displaying the Jamboard when carrying out the learning process both virtual meeting and face to face in the classroom. Google Jamboard is one of digital board where the writer can write, drew and created their ideas with use some tools in Jamboard application. Through Google Jamboard, teacher will find it easier to collect, correct, and save student’s writing project because in one link all students can write or edit the Jamboard file. So, this is very effective to use as a digital learning media, especially learning English in the form of writing skills lessons.